Pengaruh Green Accounting, CSR dan Kinerja Keuangan terhadap Nilai Perusahaan yang Terdaftar di BEI Tahun 2016-2022 - Kumala, Nidia; Priantilianingtiasari, Ruly (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Mining companies are closely related to the surrounding environment. The company's treatment of the environment must be considered. Not only the environment, companies must also pay attention to social issues as well. This study aims to analyse and determine 1) the effect of green accounting on firm value, 2) the effect of CSR on firm value, 3) the effect of financial performance on firm value, and 4) the effect of green accounting, CSR and financial performance on the value of mining companies listed on the Indonesia Stock Exchange in 2016-2022. The method in this study uses quantitative methods with the sampling technique used in is purposive sampling by obtaining 7 companies with a total of 49 annual reports that will become objects. The data source used in this research is secondary data. Data analysis using panel data analysis using Eviews software. The test results show that financial performance has a significant effect on firm value. Green accounting and CSR have no significant effect on firm value. Simultaneously the influence of green accounting, CSR and financial performance has a significant effect on firm value. Keywords: CSR, Green Accounting, Financial Performance